1999
DOI: 10.1074/jbc.274.44.31312
|View full text |Cite
|
Sign up to set email alerts
|

Discordant Effects of Glucosamine on Insulin-stimulated Glucose Metabolism and Phosphatidylinositol 3-Kinase Activity

Abstract: The impact of increased GlcN availability on insulinstimulated p85/p110 phosphatidylinositol 3-kinase (PI3K) activity in skeletal muscle was examined in relation to GlcN-induced defects in peripheral insulin action. Primed continuous GlcN infusion (750 mol/kg bolus; 30 mol/kg⅐min) in conscious rats limited both maximal stimulation of muscle PI3K by acute insulin (I) (1 unit/kg) bolus (I ؉ GlcN ‫؍‬ 1.9-fold versus saline ‫؍‬ 3.3-fold above fasting levels; p < 0.01) and chronic activation of PI3K following 3-h e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Interestingly, when this was measured after only 2 h infusion, glucosamine had no effect [31]. In contrast to this, impaired insulin stimulation of PI3K activity was seen as early as 30 min after glucosamine infusion [33]. Despite this, there was no significant reduction in glucose uptake until 110 min of glucosamine infusion.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, when this was measured after only 2 h infusion, glucosamine had no effect [31]. In contrast to this, impaired insulin stimulation of PI3K activity was seen as early as 30 min after glucosamine infusion [33]. Despite this, there was no significant reduction in glucose uptake until 110 min of glucosamine infusion.…”
Section: Discussionmentioning
confidence: 83%
“…Of note, the rodent studies discussed above were of longer duration and in some cases involved chronic models. Indeed, although the maximal effects of insulin on tissue signaling are seen shortly after administration (42), an extended duration of about 5 h of hyperinsulinemia is needed to demonstrate its maximal whole body effects on glucose handling (43), highlighting the potential importance of more prolonged central signaling on the regulation of glucose production. Importantly, no studies to date have evaluated the time-dependent effect of CNS insulin on glucose production in rodents, and such studies would add important insights to the field.…”
Section: Evidence For Cns Nutrient and Hormone Sensing In Animalsmentioning
confidence: 99%
“…These results suggest that horizontal cell may play a role in protecting retina from external environmental or biochemical changes. It has been suggested that increased flux into the glucosamine pathway could quantitatively or qualitatively alter the O-linked glycosylation state of various proteins involved in insulin action and thereby affect their function via numerous potential mechanisms (Hawkins et al, 1999). In addition, O-linked glycosylation of serine or threonine residues can competitively inhibit phosphorylation at the same sites (Griffith et al, 1995a;Hart et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, O-linked glycosylation of serine or threonine residues can competitively inhibit phosphorylation at the same sites (Griffith et al, 1995a;Hart et al, 1996). The reciprocal glycosylation/phosphorylation state of key serine/threonine kinase could affect the tyrosine phosphorylation state and thus the activation of insulin receptor substrate-1 or other upstream signaling molecules Hawkins et al, 1999). O-Linked glycosylation can also affect the intracellular localization of proteins .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation